2017
DOI: 10.5455/jmp.20170721110820
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical parameters as indicators of antihypertensive efficacy of leaf aqueous extract of Tridax procumbens (Lin) in L-NAME induced hypertensive rats

Abstract: Background: Cardiovascular disease is a widespread public health problem and hypertension is one of the major risk factors of it. Tridax procumbens leaf extract is traditionally used in the treatment of hypertension. This study evaluates the effects of T. procumbens extract (TPE) on blood biochemical parameters of N-nitro-L-arginine methyl ester (L-NAME)-induced hypertensive rats. Materials and Methods: Rats were divided randomly into four different treatment groups. Group I received 0.9% NaCl (control), Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Furthermore, superoxide dismutase concentration was reduced in the CVS-only exposed group as compared to the EETP supplemented group (Table 1). Similar protective activity of EETP, as observed in this study, has been previously suggested by other studies 13,22 . A recent study also reported a similar observation regarding vitamin C supplementation (alone) during CVS exposure 13,14 in male and gravid female rats.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, superoxide dismutase concentration was reduced in the CVS-only exposed group as compared to the EETP supplemented group (Table 1). Similar protective activity of EETP, as observed in this study, has been previously suggested by other studies 13,22 . A recent study also reported a similar observation regarding vitamin C supplementation (alone) during CVS exposure 13,14 in male and gravid female rats.…”
Section: Discussionsupporting
confidence: 93%
“…According to the aforementioned findings, mechanisms depending on or unrelated to the endothelium are presumably what help the T. procumbens extract's vasorelaxant impact. Salahdeen et al 22 experimented to evaluate parameters used to determine the efficiency of aqueous leaf extract of Tridax procumbens (Linn.) in managing hypertension.…”
Section: Medicinal Uses Of Tridax Procumbensmentioning
confidence: 99%
“…Furthermore, a mechanistic study by Salahdeen et al 6 observed that the stimulation of prostacyclin production and opening of small conductance calciumactivated potassium channels are involved in the vasorelaxant activities of AETPL in normotensive rats. In hypertensive rats, treatment with AETPL significantly reduced arterial blood pressure in Nitric Oxide (NO) synthase inhibitor (L-NAME)-induced hypertensive male rats 7 . The ability of the Tridax procumbens leaf extract to significantly reduce arterial blood pressure in hypertensive rats opened a vista in the mechanistic study of the vasorelaxant activities of AETPL.…”
Section: Introductionmentioning
confidence: 99%